2020
DOI: 10.1589/jpts.32.467
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the dorsolateral prefrontal cortex activation, ankle muscle activities, and coactivation during dual-tasks to postural steadiness: a pilot study

Abstract: [Purpose] To examine the influence of dorsolateral prefrontal cortex (DLPFC) activation, ankle muscle activities, and coactivation on postural steadiness during dual-tasks. [Participants and Methods] A total of 14 participants (8 males, 6 females) were included. The participants stood straight on the force plate, and performed 3 different tasks: 1) a quiet standing (single-task), 2) a repetition of a number (dual-task 1: DT1), and 3) a serial subtraction (dual-task 2: DT2). We divided the participants into 2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Some similar studies to ours corroborate our results [ 5 , 15 ], but others do not [ 12 ]. For example, a study that assessed the influence of ankle muscle activities, coactivation, and dorsolateral prefrontal cortex activity on postural stability during the dual-task showed a higher tibialis anterior muscle activity and tibialis anterior–gastrocnemius lateralis coactivation in the shorter sway path length group than the longer group.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Some similar studies to ours corroborate our results [ 5 , 15 ], but others do not [ 12 ]. For example, a study that assessed the influence of ankle muscle activities, coactivation, and dorsolateral prefrontal cortex activity on postural stability during the dual-task showed a higher tibialis anterior muscle activity and tibialis anterior–gastrocnemius lateralis coactivation in the shorter sway path length group than the longer group.…”
Section: Discussionsupporting
confidence: 91%
“…For example, a study that assessed the influence of ankle muscle activities, coactivation, and dorsolateral prefrontal cortex activity on postural stability during the dual-task showed a higher tibialis anterior muscle activity and tibialis anterior–gastrocnemius lateralis coactivation in the shorter sway path length group than the longer group. Furthermore, the left dorsolateral prefrontal cortex activity was superior during the performance of the dual-task (performing calculations while standing still) than the single task [ 15 ]. Another study showed a decline in gastrocnemius and tibialis anterior muscle activity during the cognitive dual-task in young and older adults, suggesting a less attentional processing capacity available to the balance control under dual-task conditions [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the dorsolateral prefrontal cortex (DLPFC) is primarily associated with executive functions, its role in the control of posture, particularly during cognitively demanding and complex sensory tasks, is well established. [13][14][15][16] Cognitive impairments are shown to impact posture negatively by changing several variables of postural steadiness (e.g. sway velocity) and increasing the risk of accidental falls.…”
Section: Hypothesismentioning
confidence: 99%